2005
DOI: 10.4049/jimmunol.175.12.8386
|View full text |Cite
|
Sign up to set email alerts
|

Cloning the Arterial IgA Antibody Response during Acute Kawasaki Disease

Abstract: Kawasaki disease (KD) is the most common acquired cardiac disease in children in developed nations. The etiology of KD is unknown but likely to be a ubiquitous microbial agent. Previously, we showed that oligoclonal IgA plasma cells infiltrate coronary arteries and other inflamed tissues in acute KD. We demonstrated that a synthetic Ab made using an α H chain sequence prevalent in acute KD arterial tissue detected Ag in acute KD coronary arteries, lung, and other inflamed tissues and that Ag localized to cytop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 18 publications
2
22
0
1
Order By: Relevance
“…The etiology of KD remains unknown despite 40 years of intensive studies, although the current paradigm is that KD is triggered by an infectious agent that elicits an inflammatory response directed at cardiovascular tissues in genetically susceptible hosts 2, 11 . 3, 4, 12 …”
Section: Introductionmentioning
confidence: 99%
“…The etiology of KD remains unknown despite 40 years of intensive studies, although the current paradigm is that KD is triggered by an infectious agent that elicits an inflammatory response directed at cardiovascular tissues in genetically susceptible hosts 2, 11 . 3, 4, 12 …”
Section: Introductionmentioning
confidence: 99%
“…79 The limited understanding of the etiologic agent(s) and cellular and molecular pathology of vasculitis, continues to thwart development of more efficacious treatments or cures. 1012 …”
mentioning
confidence: 99%
“…By examining tissue samples from fatal cases of KD, recent progress has been made in understanding KD aetiology and pathogenesis [17][18][19][20][21][22] . These studies revealed that oligoclonal IgA plasma cells infiltrate inflamed tissues, including coronary arteries 17,18 .…”
mentioning
confidence: 99%